Why Literature? Devkota and Vargas Llosa on Literature - Upadhyay, Hriseekesh (The Harvest, 2024)
Literature along with music and arts is viewed in both Eastern and Western tradition as an essential mark of civilized human beings. Lacking any of these would render a human to the level of animal existence. We all aspire to rise to the higher level than that. Literature makes us understand our inner feelings and helps us overcome our darker inclinations. It enlightens us about what might be rumbling in the minds of fellow human beings. Literature composed in ancient times or in our own living era, literature of the distant continents or our own homeland makes us evolve into better human beings. The predominance of science and technology in our times makes literature even more important for the mental health and general well-being of humanity.